Tradisi Lokal dan Interaksi Sosial sebagai Fondasi Harmonisasi Muslim dan Non-Muslim - Wiwit Nopriani; Mohd Arifullah; Adi Iqbal (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the phenomenon of harmonization between Muslim and Non-Muslim communities in Cermin Nan Gedang District using a qualitative descriptive approach through observation, interviews, and documentation. Data were analyzed using reduction, presentation, and verification, and employing Nurcholis Madjid's theory. The findings reveal strong harmonization, evident in cooperation during religious holiday commemorations, traditional events, and weddings, where mutual assistance and helping one another are key practices. Driving factors include social interaction that does not prioritize religious differences, interfaith marriages that strengthen brotherhood, and collective awareness of the importance of unity. The impact is reflected in peaceful and harmonious coexistence. The study concludes that the local community successfully maintains harmony despite differing beliefs, as they prioritize humanitarian and social values above religious boundaries. This harmonization serves as a sustainable model of tolerance, reinforced by local traditions and the awareness that unity is the foundation for a stable and prosperous communal life.